Physical violence during pregnancy in Peru: Proportion, geographical distribution and associated factors, 2016-2018 - Nuñez-Ochoa, Mercedes Joselyn (2022)
Background: Physical violence during pregnancy is a poorly evaluated sensitive public health problem that, additionally, is related to various perinatal complications. The objective is to estimate the proportion, geographic distribution and sociodemographic factors associated with physical violence during pregnancy between 2016 and 2018. Material and methods: Secondary baseline analysis of the Demographic and Family Health Survey (ENDES), which included respondents who answered whether or not they had experienced physical violence during pregnancy in the last 12 months. Results: The proportion of physical violence was 9,9% [95%CI:9,6-10,4%] during 2016, 9,2% [95%CI:8,8-9,6%] during 2017 and 8,6% [95%CI:8,3-8,9%] during 2018, The regions with the highest proportion were Puno, Arequipa, and Apurímac during the 3 years. Among the associated factors, the residue in rural areas (PR:0,49; p=0,011) and be “very rich” (PR:0,63; p=0,029) was protective; while they were at risk of not presenting studies (PR:1,87; p=0,014), the cohabiting marital status (PR:1,51; p=0,001), separated (PR:3,56; p<0,001), showing an age between 40 a 49 years (PR:1,79; p=0,012) and that partner drinks alcohol (RP:1,61; p<0,001). Conclusions: The proportion of violence in Peru has been decreasing in recent years, presenting higher indicators in the south of the country. The factors that predispose this phenomenon are the wealth index, educational level, marital status, and the age of the pregnant woman.